Gender Dan Leadership Aspiration: Pengaruh Dari Communal Orientation Dan Organizational Identification - Febiola Febiola; Ronnie Resdianto Masman (Jurnal Manajerial Dan Kewirausahaan, 2020)
This research was conducted in order to determine and understand the impact of gender toward leadership aspiration mediated by communal orientation, and organizational identification toward leadership aspiration and the moderating effect of it in the environment of coffee shop employee based in North Jakarta. This research implements survey method, in which questionnaires were used as tools to collect the data needed for this research. A total of 80 respondents participated in this research, were then analysed using PLS-SEM method using SmartPLS 3.2.7 Software. Based on the results of the data analysis, it was found that gender is a significant predictor toward leadership aspiration mediated by communal orientation, and organizational identification is a significant predictor toward leadership aspiration and has a moderating effect toward the impact of communal orientation toward leadership aspiration. Theoretical and practical contributions are discussed. Penelitian ini dilakukan guna mengetahui dan memahami pengaruh gender terhadap aspirasi kepemimpinan yang dimediasi oleh orientasi komunal, dan identifikasi organisasi terhadap aspirasi kepemimpinan serta efek moderasinya di lingkungan pekerja kedai kopi di Jakarta Utara. Penelitian ini mengimplementasikan metode survei, dimana kuesioner digunakan sebagai alat untuk mengumpulkan data dari responden. Sebanyak 80 responden berpartisipasi pada penelitian ini, kemudian diolah dengan metode PLS-SEM dengan bantuan perangkat lunak SmartPLS versi 3.2.7. Berdasarkan hasil analisis data, dapat disimpulkan bahwa gender adalah prediktor yang signifikan terhadap aspirasi kepemimpinan yang dimediasi oleh orientasi komunal, dan identifikasi organisasi adalah prediktor yang signifikan terhadap aspirasi kepemimpinan dan memiliki efek moderasi terhadap hubungan antara orientasi komunal dan aspirasi kepemimpinan. Kontribusi teori dan praktik dibahas dalam penelitian ini.